Cover Image, Volume 115, Number 5, May 2018. Issue 5 (25th March 2018) - Grein, Tanja A.; Loewe, Daniel; Dieken, Hauke; Salzig, Denise; Weidner, Tobias; Czermak, Peter
Abstract : The cover image, by Tanja A. Grein et al., is based on the Article High titer oncolytic measles virus production process by integration of dielectric spectroscopy as online monitoring system, DOI:10.1002/bit.26538 .